1992
DOI: 10.3109/02656739209005023
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric properties of human glioma and surrounding tissue

Abstract: Dielectric properties of human glioma and surrounding tissue from five patients were measured. Experiments were performed at frequencies of 5-500 MHz at 24 +/- 0.5 degrees C using a Network Analyser and a coaxial line capacitive sensor. The permittivity and conductivity of tumours were 30% higher than that of the surrounding tissues due to their higher water content. The characteristic of less differentiation in tumours clearly was reflected in the dielectric properties, namely a smaller parameter for the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 7 publications
4
49
0
Order By: Relevance
“…Several studies that measured dielectric tissue properties at radiofrequencies found significantly higher electrical conductivity of cancerous compared to normal liver tissue [6][7][8][9]13]. This difference becomes more pronounced at lower frequencies, especially below 100 kHz (see Figure 2).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Several studies that measured dielectric tissue properties at radiofrequencies found significantly higher electrical conductivity of cancerous compared to normal liver tissue [6][7][8][9]13]. This difference becomes more pronounced at lower frequencies, especially below 100 kHz (see Figure 2).…”
Section: Discussionmentioning
confidence: 89%
“…Smith et al [7] measured liver carcinoma ex vivo between 1 kHz and 13 MHz from a rabbit model and found 6-7.5 times higher electrical conductivity at low frequencies, but 2-5 times lower permittivity compared to normal liver tissue. Lu et al [8] measured human glioma and surrounding tissue ex vivo between 5-500 MHz and found 30% higher permittivity and conductivity in tumours compared to surrounding tissue. They also calculated power absorption between tumour and normal tissue and found that-depending on the direction of the electromagnetic wave-power was absorbed preferentially by either tumour or normal tissue.…”
Section: Introductionmentioning
confidence: 98%
“…Initial, single cases of brain tumors have been reported for 1.5 T [53] and 7 T [54]. All cases show a tumor conductivity increased roughly by a factor of two compared with the surrounding white matter, as expected from [55]. In [54], the hypothesis is raised that the tumor conductivity correlates with its sodium content.…”
Section: Ept Experimentsmentioning
confidence: 80%
“…Conductivity and permittivity values at 200 kHz were obtained through an extensive literature search for all the tissues represented in the model: scalp (Gabriel et al 1996, Hemingway and McClendon 1932, Yamamoto and Yamamoto 1976, Burger and van Milaan 1943), skull (De Mercato and Garcia Sanchez 1992, Kosterich et al 1983, Reddy and Saha 1984, Law 1993), CSF (Gabriel et al 1996, Baumann et al 1997, Crile et al 1922), GM and WM (Logothetis et al 2007, Ranck 1963, Gabriel et al 2009, Stoy et al 1982, Surowiec et al 1986, Van Harreveld et al 1963, Freygang and Landau 1955, Latikka et al 2001), and tumour (Peloso et al 1984, Surowiec et al 1988, Lu et al 1992, Latikka et al 2001). The ventricles were assumed to be filled with CSF.…”
Section: Methodsmentioning
confidence: 99%